The neuromuscular responses in patients with Parkinson's disease under different conditions during whole-body vibration training - Chia-Ming Chang; Chon-Haw Tsai; Ming-Kuei Lu; Hsin-Chun Tseng; Grace Lu; Bey-Ling Liu; Hsiu-Chen Lin (BMC, 2022)
Abstract Background Whole-body vibration (WBV) training can provoke reactive muscle response and thus exert beneficial effects in various neurological patients. This study aimed to investigate the muscles activation and acceleration transmissibility of the lower extremity to try to understand the neuromuscular control in the Parkinson's disease (PD) patients under different conditions of the WBV training, including position and frequency. Methods Sixteen PD patients and sixteen controls were enrolled. Each of them would receive two WBV training sessions with 3 and 20 Hz mechanical vibration in separated days. In each session, they were asked to stand on the WBV machine with straight and then bended knee joint positions, while the vibration stimulation was delivered or not. The electromyographic (EMG) signals and the segmental acceleration from the lower extremity were recorded and processed. The amplitude, co-contraction indexes (CCI), and normalized median frequency slope (NMFS) from the EMG signals, and the acceleration transmissibility were calculated. Results The results showed larger rectus femoris (RF) amplitudes under 3 Hz vibration than those in 20 Hz and no vibration conditions; larger tibialis anterior (TA) in 20 Hz than in no vibration; larger gastrocnemius (GAS) in 20 Hz than in 3 Hz and no vibration. These results indicated that different vibration frequencies mainly induced reactive responses in different muscles, by showing higher activation of the knee extensors in 3 Hz and of the lower leg muscles in 20 Hz condition, respectively. Comparing between groups, the PD patients reacted to the WBV stimulation by showing larger muscle activations in hamstring (HAM), TA and GAS, and smaller CCI in thigh than those in the controls. In bended knee, it demonstrated a higher RF amplitude and a steeper NMFS but smaller HAM activations than in straight knee position. The higher acceleration transmissibility was found in the control group, in the straight knee position and in the 3 Hz vibration conditions. Conclusion The PD patients demonstrated altered neuromuscular control compared with the controls in responding to the WBV stimulations, with generally higher EMG amplitude of lower extremity muscles. For designing WBV strengthening protocol in the PD population, the 3 Hz with straight or flexed knee protocol was recommended to recruit more thigh muscles; the bended knee position with 20 Hz vibration was for the shank muscles.